2011
DOI: 10.1186/1742-2094-8-179
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-I peptides act centrally to decrease depression-like behavior of mice treated intraperitoneally with lipopolysaccharide

Abstract: Centrally administered insulin-like growth factor (IGF)-I has anti-depressant activity in several rodent models, including lipopolysaccharide (LPS)-induced depression. In this study we tested the ability of IGF-I and GPE (the N-terminal tri-peptide derived from IGF-I) to alter depression-like behavior induced by intraperitoneal (i.p.) administration of LPS in a preventive and curative manner. In the first case, IGF-I (1 μg) or GPE (5 μg) was administered i.c.v. to CD-1 mice followed 30 min later by 330 μg/kg b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 68 publications
(104 reference statements)
2
47
1
Order By: Relevance
“…were measured. This protocol has been adapted from several previously published protocols [26][27][28]. Preference was calculated as: saccharin preference % = [saccharin cons./(saccharin cons.…”
Section: Saccharin Preference Test: Anhedonia (Depression-like)mentioning
confidence: 99%
“…were measured. This protocol has been adapted from several previously published protocols [26][27][28]. Preference was calculated as: saccharin preference % = [saccharin cons./(saccharin cons.…”
Section: Saccharin Preference Test: Anhedonia (Depression-like)mentioning
confidence: 99%
“…Deficits in both central and peripheral IGF-1 levels may contribute to the development of affective disorders in humans and lead to the progression of depression-like symptoms in animals (Mitschelen et al, 2011). Furthermore, IGF-1 displays antidepressant-like properties: intracerebroventricular administration of IGF-1 reverses lipopolysaccharide (LPS)-evoked depression-like behavior in rodents (Park et al, 2011). It has been shown that lipopolysaccharide (LPS)-a nonspecific immune response activator-administered intraperitoneally causes alterations in cytokine levels and leads to behavioral disturbances known as "sickness behavior".…”
Section: Introductionmentioning
confidence: 99%
“…TNF within the brain can derive from peripheral expression, expression within the brain dependent on neural input (Marquette et al, 2003), secretion within the brain in response to humoral stimuli by PAMPs or cytokines (Bluthé et al, 2002;Churchill et al, 2006;Park et al, 2011b) or exogenous addition to the brain (Bluthé et al, 2006). Current dogma suggests that all sources have the same behavioral effect: TNF induces sickness behavior, reminiscent of the actions of IL-1.…”
Section: Tnf and Behaviormentioning
confidence: 99%
“…) or peripheral (i.p.) LPS induces a depressive-like phenotype when quantified as increased time of immobility in the TST and FST (Park et al, 2011a;Park et al, 2011b). The increased time of immobility in these tests is frequently used as an index of despair.…”
Section: Tlr2 Heterodimers and Tlr4: Membrane Lipidsmentioning
confidence: 99%
See 1 more Smart Citation